(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The main objectives of the project titled, ‘A study of Beekeeping in Bhudargad tehsil, Kolhapur district’ are to study various problems in beekeeping and to give suggestions for improvement to these problems as well as existing practices. The researcher collected the relevant primary data by using questionnaire method and interaction with the sample size of fifty beekeepers chosen by Simple random sampling technique.Basic analysis was done through pie charts and bar charts to reveal the real picture in terms of percentage so that suggestions could be thought upon the concrete base. It is observed from the survey that beekeeping is not the main profession for most of the people in which involvement of women, young people and qualified adults is very less. The main problem in beekeeping is a disease called Sacbrood which impacts on the colonies as well as honey production. Beekeepers don’t know how to prevent colonies from this diseaseand they do not get any guidance regarding the same. Almost all of the beekeepers use subsidy from government and they face no problem in getting it. Majority of the beekeepers do not focus on taking byproducts. Majority of them do not want to keep beekeeping as a full time profession because of these problems. It is suggested by the researcher that government mediators likeKVIB should focus more on the trainingof beekeepers for improvement in production of honey as well as other byproducts, prevention of diseases,use of modern tools in beekeepingand marketing of products.The researcher has suggested the beekeepersthat sac brood disease was controlled by the smoke generated by the burning of Sulphur and givingthat smoke to the affected colonies.